Peran pembelajaran organisasi dan kedisiplinan terhadap kinerja guru melalui prestasi kerja pada guru sekolah dasar di Cilegon - Muafidah, Muafidah; Yusuf, Furtasan Ali; Hayadi, Herawan; Suparmoko, Muhamad; Sari, Gema Ika; Fatimah, Fatimah (Universitas Muhammadiyah Magelang, 2024)
This study aims to analyze the role of organizational learning and discipline on teacher performance by considering teacher performance as a mediating variable in elementary schools in Cilegon City. Organizational learning is an effort made by schools to improve teacher skills and knowledge through various training programs and professional development. Teacher discipline reflects the level of compliance with the rules and regulations that apply in the school environment. Teacher performance is measured based on the achievement of work results, innovation in teaching, and contribution to the school environment. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 118 teachers in several elementary schools in Cilegon City as research samples. Data analysis was carried out using regression techniques and path analysis to test direct and indirect relationships between variables. The results of the study indicate that: 1) organizational learning has a positive and significant effect on teacher performance. 2) Discipline also plays an important role in improving teacher performance. 3) Teacher performance was found as a mediating variable that strengthens the relationship between organizational learning and discipline on teacher performance. 4) These findings indicate that improving teacher performance can be achieved through the development of effective organizational learning and the implementation of strict discipline. This study provides practical implications for school administrators and educational policy makers to design professional development programs that focus on organizational learning and discipline enforcement to improve the quality of teacher performance